Historical-philosophical basis of the epistemological system by Nicolas of Cusa - Yarosh, Oleksiy (Actual Problems of Mind, 2017)
The author analyses historical and cultural preconditions of developing the epistemological conception by Nicolas of Cusa. By explicating its ideological sources the author concludes that Nicolas of Cusa has proposed a new vision of the problem of obtaining the knowledge of God by synthesizing the rational and irrational philosophical traditions.